2015
DOI: 10.1155/2015/593819
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Pertussis Incidence by Income among Oregon Teens during an Outbreak

Abstract: That disease and poverty are connected is a cornerstone of public health thought. In the case of pertussis, however, it is possible that the expected relationship to poverty is reversed. Grounds exist for considering that increases in income are associated with increases in pertussis rates, both in terms of real risk through social and network features and through the possibility of greater likelihood of care seeking and detection based on income. Using reported adolescent pertussis cases from a 2012 outbreak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…Our study found that vaccine hesitancy was higher in individuals among those with lower monthly incomes. This finding contrasts with previous research which has found that those with higher income tend to have higher vaccine hesitancy, lower vaccine coverage ( 30 , 31 ), and higher incidence of vaccine-preventable disease ( 32 ). However, other studies have found no such relationship ( 33 , 34 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our study found that vaccine hesitancy was higher in individuals among those with lower monthly incomes. This finding contrasts with previous research which has found that those with higher income tend to have higher vaccine hesitancy, lower vaccine coverage ( 30 , 31 ), and higher incidence of vaccine-preventable disease ( 32 ). However, other studies have found no such relationship ( 33 , 34 ).…”
Section: Discussioncontrasting
confidence: 99%
“…2 Most of these deaths occur in low-and middle-income countries (LMICs), and the existing paradigm is that these deaths, along with the hundreds of millions of cases of VPDs, arise due to the lack of vaccine access for families in these countries. 3,4 Recently though, the United States has seen large outbreaks of VPDs for which vaccines have been readily available for decades such as pertussis [5][6][7] and measles. 5,8 The voluntary choice not to vaccinate is especially seen in the wealthier and more educated sectors of the population, whereas outbreaks of VPDs in middle-income countries such as China (such as a large mumps outbreak in 2011-2012) 9 is due to a lack of access to vaccines.…”
Section: Introductionmentioning
confidence: 99%